2019
DOI: 10.3390/su11205718
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Decarbonisation Investment for Firms towards Environmental Sustainability

Abstract: We develop a mixed-integer non-linear programming model for firms' decarbonisation investment decision-making towards a sustainable environment. Our model seeks the optimal investment for a firm to achieve maximum profit under constraints derived from its environmental protection awareness and the government's taxation policy. We use an uncertainty theory to formulate the relationship of a firm's environmental protection awareness and its investment budget levels. Governments' taxation policy is modelled by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to Siebers et al (2019), although a carbon tax lowers earnings, businesses may still budget more for investments to boost profitability. The authors suggested a strategy for decision-making assistance that can assist businesses and the government's tax policy for appropriations in achieving the aim of environmental development.…”
Section: T H E a P P L I C A T I O N O F G R E E N T A X E Smentioning
confidence: 99%
See 1 more Smart Citation
“…According to Siebers et al (2019), although a carbon tax lowers earnings, businesses may still budget more for investments to boost profitability. The authors suggested a strategy for decision-making assistance that can assist businesses and the government's tax policy for appropriations in achieving the aim of environmental development.…”
Section: T H E a P P L I C A T I O N O F G R E E N T A X E Smentioning
confidence: 99%
“…This is a response to their desire to protect the environment. Many nations have imposed green taxes, albeit they haven't yet achieved their goal (Siebers et al, 2019). Governments must provide support tools to allow businesses to be profitable while also being sustainable in order to reduce their negative environmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…New challenges related to energy security resulting from the international geopolitical situation [2,3] and experience in implementing competitive electricity and gaseous fuels markets entail the need to update the energy forecast also for Poland and to formulate a new energy strategy [4,5]. To meet the environmental protection requirements [6], especially in reducing atmospheric pollution causing global warming [7], Poland had to assess its capabilities in this regard [8]. This contributed to the implementation of changes in the energy policy up to 2040 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies used a mathematical modeling approach to find the best investment decisions. In general, the investment modeling approaches can be divided into two types: (1) studies that maximize the effects of the investments while considering the limited budget [30][31][32] and (2) studies that minimize the total investment costs, while ensuring a certain service level of the improved system [33,34]. Our study uses the earlier investment modeling approach and introduces a novel way to evaluate the investment effects in subsequent years after the investment period for the container port development case.…”
mentioning
confidence: 99%